2019
DOI: 10.3390/ijerph16132347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air Pollution on Lung Innate Lymphoid Cells: Review of In Vitro and In Vivo Experimental Studies

Abstract: Outdoor air pollution is associated with respiratory infections and allergies, yet the role of innate lymphoid cells (ILCs) in pathogen containment and airway hyperresponsiveness relevant to effects of air pollutants on ILCs is poorly understood. We conducted a systematic review to evaluate the available evidence on the effect of outdoor air pollutants on the lung type 1 (ILC1) and type 2 ILCs (ILC2) subsets. We searched five electronic databases (up to Dec 2018) for studies on the effect of carbon monoxide (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Studies in mice have revealed that DEP, O 3 , and multi-wall carbon nanotubes activate ILC2s to produce IL-5 and IL-13 in response to IL-33 produced by airway epithelial cells. 4 In the current study, only PM 10 levels positively correlated with the proportion of ILC2s. However, previous studies showed that O 3 , a potent oxidizing agent, induced type 2 cytokine secretion from ILC2s.…”
Section: The Effect Of Air Pollutants On Airway Innate Immune Cells In Patients With Asthmamentioning
confidence: 41%
“…Studies in mice have revealed that DEP, O 3 , and multi-wall carbon nanotubes activate ILC2s to produce IL-5 and IL-13 in response to IL-33 produced by airway epithelial cells. 4 In the current study, only PM 10 levels positively correlated with the proportion of ILC2s. However, previous studies showed that O 3 , a potent oxidizing agent, induced type 2 cytokine secretion from ILC2s.…”
Section: The Effect Of Air Pollutants On Airway Innate Immune Cells In Patients With Asthmamentioning
confidence: 41%
“…In terms of immune effects, decreased levels of IFN-γ (important for macrophage activation) were observed in the peripheral blood of mice exposed to traffic pollution in China [12], and in the peripheral blood of humans exposed to diesel exhaust [33]. Further research has also observed dysregulation of the epithelial cell junction, respiratory microbiome and cytokine response as additional factors increasing pathogenic virulence in the setting of PM exposure [34].…”
Section: Discussionmentioning
confidence: 99%
“…At the levels of mucus producing cells (goblet cells), PM results in MUC5B hypersecretion (103). Furthermore, PM engages and functionally impacts innate like cells type 1 (ILC1), thereby blunting their interferon gamma (IFN-γ) production and cytotoxic function; induces antigen-presenting cell-mediated inflammatory responses, while impairing their migration; enhanced neutrophil and eosinophil responses; and shifts lymphocyte differentiation toward an effector phenotype (Th1-like) (108)(109)(110)(111). Lastly, the effects on endothelial function (disruption of tight junctions) have significant repercussion on the susceptibility to cardiovascular disease and infarction (112)(113)(114)(115).…”
Section: Cell Type-specific Responsesmentioning
confidence: 99%